Prevalence of Anemia in Children Aged Six Months to Thirty Six Months - A Hospital Based Study (Bangladesh Journal of Child Health, 2017)
Background: Anemia is a common problem in childhood, especially children aged 6months to 24 months old. In Bangladesh overall, 68 % of children aged 6-59 months are anemic. Anemia impairs normal development, decreases physical exercise tolerance & intellectual performance in children which may lead to a slowdown of growth in children. It constitutes a major public health problem in young children in the developing world with wide social & economic implications.Objective: To see the prevalence of anemia among hospitalized children aged 6 months to 36 months.Methodology: Children 6 months 36 months aged who were admitted in Dhaka Shishu (Children) hospital due to some acute illness, were enrolled from 1st June, 2010 to 30th August, 2010. Children were classified as anemic when Hb level was